SARS-CoV-2 vaccine in patients with thymic epithelial tumours with and without active or pre-existing autoimmune disorders: Brief report of a TYME network safety analysis. (May 2022) - Giugliano, Federica; Zucali, Paolo A.; Galli, Giulia; Ballatore, Zelmira; Corti, Chiara; Aliaga, Pamela T.; Uliano, Jacopo; Vivanet, Grazia; Curigliano, Giuseppe; Conforti, Fabio; Queirolo, Paola; Berardi, Rossana; et al.
Abstract: Background: International guidelines recommend severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) vaccine for patients with cancer. A substantial risk of developing vaccine-related autoimmune toxicities could be hypothesised for patients with thymic epithelial tumours (TETs) due to their high risk of autoimmune disorders (ADs). Moreover, a cross-reaction between SARS-CoV-2 spike protein antibodies and various tissue proteins has been shown, and antibodies against nucleoproteins showed overlaps in the autoimmune cross-reaction with antibodies to spike protein. Due to the rarity of TETs, no data addressing this hypothesis are available. Methods: Patients with TETs who received SARS-CoV-2 vaccine, treated in 4 referral centres of the Italian Collaborative Group for ThYmic MalignanciEs (TYME) network between February 2021 and September 2021, were interviewed through a standardised 15-items questionnaire in order to describe the safety of SARS-CoV-2 vaccine in patients affected by TETs. Results: Data from 245 doses of vaccine administered to 126 patients (41 = thymic carcinoma, 85 = thymoma; 38 with AD, of which 26 with active AD) were collected. Nine patients had a previous COVID-19-positive swab. No cases of AD reactivation or worsening of a pre-existing AD were seen in the study population. A new diagnosis of myasthenia gravis likely unrelated to the vaccine was made in two patients after the vaccination. Sixty-four patients (51%) experienced a total of 103 adverse events, all G1/G2, most commonly fatigue, new or worsening muscle pain and chills. None AE required patients' hospitalisation. Conclusions: SARS-CoV-2 mRNA vaccines appear to be safe in patients with TET, even in case of active or pre-existing AD. Highlights: Thymic epithelial tumours (TETs) induce higher risk for autoimmune diseases. Evidence on safety profile of COVID vaccines in TET patients is limited. Our data suggest that safety profile for TET patients is similar to general population. COVID-19 vaccination is safe and strongly recommended in patients affected by TET.